Assessing chemical, biological, radiological and nuclear threats to the food supply chain. Issue 1 (1st January 2018) - Meulenbelt, Stephanie
ABSTRACT: The food supply chain may be intentionally compromised. Potential devastating effects of attacks with chemical, biological, radiological or nuclear (CBRN) agents are particularly emphasised and the ease with which such an attack may take place is described in numerous sources. Yet, using the food chain's carrying capacity to spread a CBRN contamination across a wide geographic area is (extremely) complicated. Although episodes of intentional food contaminations can be serious, they rarely result in mass fatalities. Economic damage may quickly arise, but is often a result of (too) rigorous countermeasures. Past incidents demonstrate that a sole suspicion or even rumour of food being contaminated can already have severe consequences. This paper provides insight into the threat of intentional CBRN contamination of the food chain. It describes various parameters, including the type of agents capable of yielding damage, possible points of introduction and potential consequences of deliberate CBRN contamination of the food chain, in an effort to facilitate future risk assessment.